Herbal antioxidants in dialysis patients: a review of potential mechanisms and medical implications. Issue 1 (1st January 2021) - Asgharpour, Masoumeh; Alirezaei, Amirhesam
Abstract: The consumption of exogenous antioxidants isolated from herbal extracts has shown beneficial effects on ameliorating dialysis-related complications through debilitating oxidative stress and inflammatory process. Many clinical studies available in public databases have reported the improved consequences of dialysis in patients supplemented with herbal antioxidants. Exploration of such data offers great possibilities for gaining insights into the potential mechanisms and medical implications of herbal antioxidants. In this work, the mechanisms and implications of some famous bioactive substances including silymarin, curcumin, resveratrol, emodin, and quercetin on the consequences of dialysis in chronic kidney disease (CKD) patients were explored. The protective features of silymarin are due to the flavonoid complex silybin. Curcumin is an active element from the root of curcuma longa with extensive beneficial properties, including antioxidant, anti-inflammatory activity, and inhibitory effects on cell apoptosis. Resveratrol can reduce the oxidative stress by neutralization of free radicals. Emodin is known as a natural anthraquinone derivative isolated from Chinese herbs. Finally, quercetin has been reported to exhibit several properties including antioxidant, anti-diabetic, analgesic, antihistaminic, antiviral, cholesterol reducer, and renal hemodynamic modulator. However, potential mechanisms and medical implications of the aforementioned herbal antioxidants seem to be more complicated, that is, more studies are required in this field.